An inconvenient status in anti-osteoporotic treatment process: corticosteroid use - Öztürk,Ercüment (2022)
SUMMARY OBJECTIVE: There are limited studies investigating the comparison of the efficacy of anti-osteoporotic drugs in different conditions resulting in osteoporosis in older adults. This study aimed to compare the effectiveness of anti-osteoporotic agents in older adults with or without glucocorticoid-induced osteoporosis. METHODS: This retrospective study included 364 patients with osteoporosis, aged 65 years and older. Bone mineral density measurement was performed, and the percent change from baseline was calculated at month 24. RESULTS: Of the 364 patients, 80 were glucocorticoid users. Similar changes in the bone mineral density of the lumbar spine and femoral neck and fracture risk were found in patients with or without glucocorticoid-induced osteoporosis. There was no significant difference in bone mineral density changes between the groups in terms of anti-osteoporotic agents used. CONCLUSIONS: This study demonstrated that the response to anti-osteoporotic agents was similar in older adults with glucocorticoid-induced osteoporosis and those without glucocorticoid-induced osteoporosis. The results of our study may guide osteoporosis treatment in older individuals with glucocorticoid-induced osteoporosis.